SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT KANDUNGAN MENGGUNAKAN METODE FORWARD CHAINING - Ridwansyah Ridwansyah (Jurnal Techno Nusa Mandiri, 2016)
The womb is an organ the body that is highly important in the life of a woman who serves as a place for seed candidates baby, But lack of information about diseases content will cause new woman know the presence of a disease the womb inside of them after an advanced stage. The expert system needed to know disease early content by producing an output of the possibility of disease what suffered based on symptoms felt by the user. This system uses a method of the search for fore ( forward chaining to find the solution or the possibility of disease suffered by the user.